Osteoporotic fractures of proximal femur: clinical and epidemiological features in a population of the city of São Paulo - Ramalho, Ana Claudia; Lazaretti-Castro, Marise; Hauache, Omar; Vieira, José Gilberto; Takata, Edmilson; Cafalli, Francisco; Tavares, Fernando (São Paulo Medical Journal, 2001)
CONTEXT: It is believed that about 25% of menopausal women in the USA will exhibit some kind of fracture as a consequence of osteoporosis. Fractures of the proximal femur are associated with a greater number of deaths and disabilities and higher medical expenses than all the other osteoporotic fractures together. OBJECTIVE: To study the clinical and epidemiological features of patients with proximal femur fracture in hospitals in São Paulo. DESIGN: Transversal and retrospective study. LOCAL: Hospital São Paulo and Hospital Servidor Público Estadual “Francisco Morato Oliveira”. PARTICIPANTS: Patients aged sixty-five years or more hospitalized because of proximal femur fracture, from March to November 1996 (N = 73). This group was compared to patients of the same age without fracture of the proximal femur. INTERVENTION: Evaluation of weight, height, body mass index; lifestyle habits (physical activity at home, ingestion of dairy calcium, drinking of coffee, smoking habit), gynecological history (ages at menarche and menopause, number of pregnancies and lactations), previous morbidity, use of medications, history of previous fractures, family history of osteoporosis. MEASUREMENT: The comparison of the different data regarding lifestyle habits between the two groups was made using the chi-squared test. Other data were analyzed using the Mann – Whitney test. P £ 0.05 was considered significant. RESULTS: We noted a predominance of proximal femur fracture among females in relation to males (a female/male ratio of 3.3:1) with a progressive increase in the frequency of proximal femur fracture with age in both sexes. The group with proximal femur fracture, in comparison with the control group, showed a lower body mass index, less physical activity, and a greater number of pregnancies and lactations. Other data were not different. CONCLUSION: In accordance with the literature, we found a predomination of proximal femur fracture in women in relation to men, and a favorable effect of higher body mass index and physical activity for decreasing the frequency of proximal femur fracture. We also discuss the role of pregnancies and lactation on the frequency of proximal femur fracture.